Stability analysis of unsteady stagnation-point gyrotactic bioconvection flow and heat transfer towards the moving sheet in a nanofluid - Md Basir, Md Faisal; Hafidzuddin, Mohd Ezad Hafidz; Naganthran, Kohilavani; Hashim; Chaharborj, Sarkhosh Seddighi; Mohd Kasihmuddin, Mohd Shareduwan; Nazar, Roslinda (Physical Society of the Republic of China, 2020)
The present work investigated the unsteady stagnation-point flow and heat transfer of a nanofluid containing gyrotactic microorganisms past a permeable moving surface. The similarity transformations produced the mathematical model in the simpler form, which is in the form of ordinary differential equations, and the collocation method solved it numerically. The dual solutions are observable when the governing parameters vary. The decelerating flow and weak effect of suction at the shrinking sheet delays the boundary layer separation. Stability analysis showed that the upper branch solution is a solution with the stabilizing feature while the lower branch solution is an unstable solution which implies the flow with separation. This theoretical study is significantly relevant to microscopic biological propulsion integrated with the nano-based system.